Accumulation of risk factors associated with poor bone health in older adults. Issue 1 (December 2016) - Zhang, Jean; Jameson, Karen; Sayer, Avan; Robinson, Sian; Cooper, Cyrus; Dennison, Elaine
Abstract Summary Clustering of factors linked with poor bone health is common in older adults and is associated with lower bone density and increased fracture risk in women. Purpose Many factors are associated with bone mineral density, which in turn is strongly linked with risk of fragility fracture. We assessed how commonly clustering of risk factors occurs and related such clustering to bone mineral density in a population of older community-dwelling men and women. Method This is a cross-sectional study with 498 men and 498 women aged 59 to 72 years, who were participants in the Hertfordshire Cohort Study, in whom incident fracture was recorded. Physical activity, diet quality, history of prior fracture, family history of fracture, cigarette and alcohol consumption and comorbidities were obtained through baseline questionnaire. Measurements of grip strength and bone mineral density of the lumbar spine and total femur were also taken. Results Clustering of risk factors was common, with over 30 % having two or more. In women, a graded association between the number of risk factors and low bone density was seen, and strong relationships were also seen between the number of risk factors and incident fracture; women with three or more risk factors had an adjusted hazard ratio (HR) of incident fracture of 5.98 (1.67, 21.43;p = 0.006) compared to women with no risk factors; women with two risk factors had an adjusted HR of 2.97 (1.14, 7.74;p = 0.03) and those with one, 2.28 (0.90, 5.75;p = 0.08). Conclusion Clustering of risk factors for poor bone health is common in community-dwelling older adults and is associated with increased risk of fracture and adverse bone health in women.